Plasma Cell Differentiation Pathways in Systemic Lupus Erythematosus - Malkiel, Susan; Barlev, Ashley N.; Atisha-Fregoso, Yemil; Suurmond, Jolien; Diamond, Betty (Frontiers in Immunology, 2018)
Plasma cells (PCs) are responsible for the production of protective antibodies against infectious agents but they also produce pathogenic antibodies in autoimmune diseases, such as systemic lupus erythematosus (SLE). Traditionally, high affinity IgG autoantibodies are thought to arise through germinal center (GC) responses. However, class switching and somatic hypermutation can occur in extrafollicular (EF) locations, and this pathway has also been implicated in SLE. The pathway from which PCs originate may determine several characteristics, such as PC lifespan and sensitivity to therapeutics. Whereas both GC and EF responses have been implicated in SLE, we hypothesize that one of these pathways dominates in each individual patient and genetic risk factors may drive this predominance. While it will be important to distinguish polymorphisms that contribute to a GC-driven or EF B cell response to develop targeted treatments, the challenge will be not only to identify the differentiation pathway but the molecular mechanisms involved. In B cells, this task is complicated by the cross-talk between the B cell receptor, Toll-like receptors (TLR) and cytokine signaling molecules, which contribute to both GC and EF responses. While risk variants that affect the function of dendritic cells and T follicular helper cells are likely to primarily influence GC responses, it will be important to discover whether some risk variants in the IFN and TLR pathways preferentially influence EF responses. Identifying the pathways of autoreactive PC differentiation in SLE may help us to understand patient heterogeneity and thereby guide precision therapy.